Wedelolactone induces growth of breast cancer cells by stimulation of estrogen receptor signalling - Nehybova, Tereza; Šmarda, Jan; Daniel, Lukas; Brezovsky, Jan; Beneš, Petr (Journal of steroid biochemistry and molecular biology, 2015)
Wedelolactone, a plant coumestan, was shown to act as anti-cancer agent for breast and prostate carcinomas in vitro and in vivo targeting multiple cellular proteins including androgen receptors, 5-lipoxygenase and topoisomerase IIα. It is cytotoxic to breast, prostate, pituitary and myeloma cancer cell lines in vitro at μM concentrations. In this study, however, a novel biological activity of nM dose of wedelolactone was demonstrated. Wedelolactone acts as agonist of estrogen receptors (ER) α and β as demonstrated by transactivation of estrogen response element (ERE) in cells transiently expressing either ERα or ERβ and by molecular docking of this coumestan into ligand binding pocket of both ERα and ERβ. In breast cancer cells, wedelolactone stimulates growth of estrogen receptor-positive cells, expression of estrogen-responsive genes and activates rapid non-genomic estrogen signalling. All these effects can be inhibited by pretreatment with pure ER antagonist ICI 182,780 and they are not observed in ER-negative breast cancer cells. We conclude that wedelolactone acts as phytoestrogen in breast cancer cells by stimulating ER genomic and non-genomic signalling pathways.
Keywords: Response Elements; nádory prsu; proliferace buněk; Female; Transcription Factor AP-1; alfa receptor estrogenů; Cell Line, Tumor; vazebná místa; Estrogen Receptor alpha; HEK293 Cells; responzivní elementy; ženské pohlaví; antagonisté estrogenového receptoru; simulace molekulového dockingu; MFC-7 buňky; Estrogen Receptor beta; lidé; Antineoplastic Agents; MCF-7 Cells; protinádorové látky; Coumarins; Breast Neoplasms; signální transdukce; Signal Transduction; HEK293 buňky; estrogeny; kumariny; transkripční faktor AP-1; Estrogens; aktivace transkripce; Cell Proliferation; beta receptor estrogenů; Estradiol; Estrogen Receptor Antagonists; Transcriptional Activation; Molecular Docking Simulation; nádorové buněčné linie; estradiol; Binding Sites; Humans